A Study on Problems and Prospects of Contract Farming in Karnataka: An Over View - Vasundara A.S., (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
This study explores the problems and prospects of contract farming in Karnataka using secondary data from published research papers, government reports, and agricultural databases. Evidence shows that contract farming has a strong positive impact on rural livelihoods, with income and employment generation nearly twice as high on contract farms compared to non-contract farms. An economic assessment across the districts of Hassan, Tumkur, Kolar, and Koppal reveals favorable benefit–cost ratios ranging from 2. 37 to 6. 18. ( Academia. edu. )The key advantages of contract farming include assured markets, access to quality inputs and technical support, lower transaction costs, higher profits, and reduced dependence on crop loans. It is particularly beneficial for small and marginal farmers, as it connects them with modern technologies and guaranteed market opportunities. Despite these benefits, several challenges continue to hinder its full potential. Farmers face delayed payments, limited credit access, water shortages, unreliable electricity supply, and difficulties in meeting quality standards. Other issues such as manipulation of grading norms, rising input costs, irregular payments, and labor shortages further complicate operations (Research Gate)Overall, the study concludes that contract farming has significant potential to drive agricultural growth in Karnataka. However, realizing this potential requires strong policy support, clear legal frameworks, and effective institutional mechanisms to ensure fairness, transparency, and trust between farmers and contracting companies.
Keywords: Karnataka agriculture; Contract farming; Challenges in Contract Farming; Model Contract Farming Act; Benefits of Contract Farming